Twins: The Importance of Chorionicity in Planning Care and Timing of Birth. Issue 2 (March 2019) - Killion, Molly M.
Abstract : Chorionicity is an important aspect of planning care and timing of birth for women pregnant with twins. Our maternity nursing expert, Molly Killion, explains various types of chorionicity and their implications.